TransLatin Joyce
XX, 260 p.
Keywords: TransLatin Joyce explores the circulation of James Joyce's work in the Ibero-American literary system. The essays address Joycean literary engagements in Spain, Portugal, Argentina, Mexico, and Cuba, using concepts from postcolonial translation studies, antimodernism, game theory, sound studies, deconstruction, and post-Euclidean physics.